Oral anticoagulant and reduced risk of dementia in patients with atrial fibrillation: A population-based cohort study - Pajaree Mongkhon (2020)
© 2020 Heart Rhythm Society Background: Whether oral anticoagulation (OAC) can prevent dementia or cognitive impairment (CI) in patients with atrial fibrillation (AF) remains unclear. Objective: The purpose of this study was to investigate the risk of dementia/CI among AF patients with and without OAC treatment. Methods: We conducted a retrospective cohort study using United Kingdom (UK) primary care data (2000–2017). Participants with newly diagnosed AF without a history of dementia/CI were identified. Inverse probability of treatment weights based on propensity scores and Cox regression were used to compare the dementia outcomes. Results: Among 84,521 patients with AF, 35,245 were receiving OAC treatment and 49,276 received no OAC treatment; of these patients, 29,282 were receiving antiplatelets. Over a mean follow-up of 5.9 years, 5295 patients developed dementia/CI. OAC treatment was associated with a lower risk of dementia/CI compared to no OAC treatment (hazard ratio [HR] 0.90; 95% confidence interval 0.85–0.95; P <.001) or antiplatelets (HR 0.84; 95% confidence interval 0.79–0.90; P <.001). No significant difference in dementia risk was observed for direct oral anticoagulants (DOACs) vs warfarin (HR 0.89; 95% confidence interval 0.70–1.14; P =.373), whereas dual therapy (OAC plus an antiplatelet agent) was associated with a higher risk of dementia/CI compared with no treatment (HR 1.17; 95% confidence interval 1.05–1.31; P =.006). Conclusion: OAC use was associated with a lower risk of dementia/CI compared to non-OAC and antiplatelet treatment among AF patients. The evidence for DOAC on cognitive function is insufficient, and further studies including randomized clinical trials are warranted.